PERENCANAAN STRATEGI BISNIS HOTEL GRAND KEISHA YOGYAKARTA - Ibnu Novel; Bambang Moertono (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
Tight competition among hotels in Special Region of Yogyakarta requires each hotel to implement its best business strategy to guarantee their business goals as targeted. The hotels, therefore, needs to manage their strategy. Strategy management is a science that learn how to manage a company in a comprehensive and integrated way; it provides reasons what make some companies achieve their glorious time and some companies do not. This research aims to formulate Business Strategic Planning for Hotel Grand Keisha in order to win competition. This research employs analytical methodology of PESTLE (Politic, Economic, Social, Technology, Legal and Environment), SWOT (Strengths, Weakness, Opportunity, Threats) by using EFAS (External Factor Analysis Summary) matrix, IFAS (Internal Factor Analysis Summary) matrix, SWOT matrix, and Grand Strategy matrix. This is qualitative descriptive research. Data collection is conducted through observation, interviews, documentation, triangulation, and literature study. Quality and rating of this research is gained through Focused Group Discussion. This research shows that Hotel Grand Keisha obtains 2.56 of EFAS – 2.52 of IFAS and place Hotel Grand Keisha on Quadrant 1 with alternative strategies of market penetration, market development, and product development.Keywords: PESTLE Analysis, SWOT Analysis, SWOT Matrix, Grand Strategy Matrix